MEDICAL AND PSYCHOLOGICAL AND PEDAGOGICAL ASPECTS OF PROVIDING HELP FOR NEUROTIC DISORDERS - Мальцева, Ольга; Дуб, Мар’яна (SWorldJournal, 2024)
In the work the main focus is on the structural components (organizational, communicative) of the program of health physical therapy complex for persons with neurotic disorders. The general measures are organization of rational regime, guaranteeing of en